New method for the evaluation of residual compressive strengths of sandwich panels via four-point bending. (September 2019) - Zhou, Gang; Leung, Hiu ling; Robinson, Ben; Zheng, Can
Highlights: Directly adapting end-loaded CAI method for sandwich panels is prohibitively expensive. Four-point bending of sandwich beams using a drilled hole is an effective alternative. Pre-conditioned beams with a single density core can fail consistently in compressive skin. 4 PB CAI method can predict the residual compressive strengths of damaged beams. Abstract: There is presently no standard test method for evaluating compression-after-impact (CAI) strengths of sandwich panels. A direct adaption of existing end-loaded CAI method for monolithic laminates by up-scaling the dimensions of a standard specimen shows little usefulness and could lead to such large sandwich panel sizes so that generating CAI design data in such approach would increase material costs significantly and hence be prohibitively expensive. This work develops a low-cost alternative via four-point bending, using a drilled hole of a selected diameter to represent impact damage. A challenge of this development for as-received sandwich beams with a core of a single constant density is to gain a deeper physical insight into desirable construction configurations, in which the compressive skin could fail in flexure consistently for given support span-to-thickness ratio. Sandwich construction encompasses a wide range of combinations of intrinsic parameters and hence some parametric study was essential, including varying skin thickness, lay-up, core density, skin material and sandwich symmetry in addition to the diameter of a hole. It was found that core density and compressive skin thickness were the major factors of significantly influencing the failure modes of the sandwich beams.